Lymphovenous anastomosis: microsurgical innovation and clinical outcomes in breast cancer-related lymphedema care - Lee, Claire J.; Hong, Eric S.; Rhee, Dana J.; Choi, Dongwon (Frontiers in Surgery, 2026)
Lymphovenous anastomosis (LVA) has emerged as an important physiologic microsurgical procedure for patients with breast cancer–related lymphedema (BCRL) with the goal of restoring lymphatic drainage rather than providing just palliative care for symptoms of swelling. A multicenter randomized controlled trial (RCT) in 2024 (N-LVA) found improvements in the Lymph-ICF physical and mental function domains, and decreased use of compression garments, despite modest changes in total quality of life (QoL) and limb volume at 6 months. Meta-analyses have found average reductions of 30%–35% in excess limb size and nearly two fewer cellulitis episodes per year after LVA and vascularized lymph node transfer (VLNT). As the surgical technology continues to improve (e.g., prophylactic LYMPHA procedures, high-resolution lymphatic imaging, robotic supermicrosurgery) and as LVA becomes more widely adopted within experienced surgical centers, precision surgery will be increasingly considered in lymphedema care. Collectively, these advancements represent a movement toward physiologic reconstruction in lymphedema care and the next initiatives will focus on patient selection and eligibility optimization, state-of-the-art surgical technology optimization, and standardizing outcome measures to achieve sustained improvements in QoL.